Direct membrane-damaging effect of ketoconazole and tioconazole on Candida albicans demonstrated by bioluminescent assay of ATP. - Anséhn, S (1984)
Bioluminescent assays of fungal ATP in cultures of Candida albicans exposed to tioconazole and ketoconazole demonstrated that intracellular ATP levels were directly related to cell viability. At high concentrations of drug, a fungicidal effect was indicated by a very rapid and heavy leakage of ATP and a simultaneous, dramatic decrease in intracellular ATP. This leakage was due to direct membrane damage, which was less pronounced after exposure to ketoconazole than to tioconazole. After exposure to lower imidazole concentrations, intracellular ATP indicated growth inhibition without significant leakage of ATP. These findings support the hypothesis that imidazole antifungal agents basically act in the same manner but at different concentrations.